Financial literacy and suboptimal financial decisions at older ages - Joelle H. Fong; Benedict SK. Koh; Olivia S. Mitchell; Susann Rohwedder (Goethe University Frankfurt, Center for Financial Studies (CFS), 2019)
Over the life-cycle, wealth holdings tend to be highest in the early part of retirement. The quality of financial decisions among older adults is therefore an important determinant of their financial security during the asset drawdown phase. This paper assesses how financial literacy shapes financial decision-making at older ages. We devised a special module in the Singapore Life Panel survey to measure financial literacy to study its relationship with three aspects of household financial and investment behaviors: credit card debt repayment, stock market participation, and adherence to age-based investment glide paths. We found that the majority of respondents age 50+ has some grasp of concepts such as interest compounding and inflation, but fewer know about risk diversification. We provide evidence of a statistically significant positive association between financial literacy and each of the three aspects of suboptimal financial decision-making, controlling for many other factors, including education. A one-unit increase in the financial literacy score was associated with an 8.3 percentage point greater propensity to hold stocks, and a 1.7 percentage point higher likelihood of following an age-appropriate investment glide path. The financial literacy score is only weakly positively linked with timely credit card balance repayment, both in terms of statistical significance and estimate size.
urn:nbn:de:hebis:30:3-515333
Keywords: D14; E21; G11; J32; 330; retirement; financial literacy; credit card debt; stock market nonparticipation; lifecycleinvestment; household portfolio